Avaliação da variabilidade da frequência cardíaca nos domínios do tempo, da frequência e do caos em recém-nascidos prematuros - Selig, Fábio Augusto (2010)
The role of Autonomic Nervous System and its components sympathic and parassympathic in the regulation of the interaction between different parts of human body has been exhaustibly discussed in scientific literature. These studies demonstrated the applicability of the Chaos Theory in different situations, diseases and ages. Objective: Apply the concepts of nonlinear dynamics and Chaos Theory to evaluate premature newborns (PT), analyzing their heart rate variability (HRV) and comparing them with healthy term newborns (TN). Methods: By using a Polar Advanced S810, 59 PT born with different gestational ages had their HRV obtained and analyzed in time (SDNN, RMSSD, SD1/SD2), frequency (VLF, LF, HF and LF/HF) and chaos domain (TAU, Lyapunov Exponent, Entropy and Hurst Exponent) variables. The premature were compared to 78 healthy term newborns. The comparison were made applying Kruskal-Wallis statistic method and their graphic demonstration made by using Box-plots. Results: All time, frequency and chaos domain variables demonstrated statistic difference comparing term and preterm newborns except Hurst Exponent. Conclusion: Preterm newborn follow the rules of chaos theory and have more linear behavior when compared with term newborn.